استخدام الشبكات العصبونية لتنبؤ بنك الدم باحتياجات مرضى سرطان الدم - عماشة, هاني; الامام, وائل; نعمان, براءة (مجلة جامعة تشرين للبحوث والدراسات العلمية- سلسلة العلوم الهندسية, 2019)
Blood banks are the main provider of the large amounts of blood to Acute Myeloid Leukemia Patients undergoing Stem Cells Treatment transplant. The bank always strives to predict the required amount so through identifying the correlations between blood analysis indicators (independent variables) that are believed to influence the success of Acute Myeloid Leukemia (AML) treatment via Stem Cells Transplantation (SCT) and between the outcome )dependent variables (of treatment which are: Hospitalization Period, Relapse of leukemic cell, and the Overall Survival. Since, as the hospitalization period and lengthens and the relapse rate increases, it means we have to get ready for another round of transplantation, and, hence, prepare new quantities of blood again and again. The overall survival gives a longer prediction period to take into consideration. If it were to be short period, a new quantity of blood is prepared anyway should an emergency occurs Influencing inputs are quite few but has to be precisely specified from an inferential statistical viewpoint in order to reduce their number. Data from two hospitals (22+20=42 patients) were collected and a sample from external hospital counted 898 patients was also studied, and Kendal Tau-b was adopted using SPSS. Eighteen indicators (independent variables) were considered, some of which: age, weight, hemoglobin, white blood cells, response to radiation therapy and to chemotherapy prior to transplantation. The study figured out all those indicators that correlates with each of the dependent (or outcome) variables mentioned above. Dependent (or outcome) variables included hospitalization, relapse, and overall survival. It has been discovered what variables has an influence on the dependent variables; or outcomes. These were used as inputs to the neural network where 85% of the sample were assigned for training, 5% for validation, and 10% for testing. Prediction accuracy reached 88% which is a very good result, with nearly 20 neurons and 12 epochs to reach that result. Gradient has also dropped to very small bottom (0.00125) and Regression was 70%, which has not been available to the physician before. Equipped with this decision aiding tool, the physician can rethink the transplantation protocol. The project has, thus, achieved its goal which is providing a decision support system that enables blood bank managers to reserve such an ever-increasing amount of blood bags for those patients. يهتم بنك الدم بتأمين احتياجات مرضى سرطان الدم. ويسعى دوما للتنبؤ بهذه الاحتياجات من خلال تحديد بعض المتغيرات المستقلة التي تسهم بالتأثير بدرجات متباينة على نتائج علاج سرطان نقي الدم الحاد بالخلايا الجذعية التي تنحصر بمتغيرات تابعة (غير مستقلة) هي فترة الاستشفاء والنكس والبقيا. إذ أنه كلما طالت فترة الاستشفاء وزاد معدل النكس فهذا يدل على أننا يجب أن نستعد لجولة أخرى من الزرع وبالتالي تحضير كميات جديدة من الدم. كذلك الأمر بالنسبة للبقيا الذي ينبئنا بأن هذا المريض سيتجاوز محنته بعد الزرع الأول وبالتالي لن يحتاج لكميات دم جديدة. أما إذا كان البقيا قصيرا فقد نبادر لجولة علاج وتحضير كميات دم احتياطا لأنه وإن كان المريض محتملا وفاته بأي لحظة سنحاول محاولة أخيرة وهذا طبعا يستلزم كميات دم. تم تحديد المشعرات (المتغيرات المستقلة)، المتوقع ان تسهم بشكل فاعل في نتائج العلاج، بدقة من وجهة نظر إحصائية استدلالية لأجل تقليص عددها وبهذا يقل تكرار العوامل المترابطة. بلغ حجم العينة المحلية 42 مريضا من مشفيين محلييّن أمّا العيّنة الخارجيّة فحصلنا عليها من مشفى آخر وعددها 898 واستعملت طريقة معامل ترابط كندال-تاو-ب التراتبي لكشف الارتباط الاحصائي بين المتغيرات المستقلة بحد ذاتها، ثم كشف الارتباط بين المتغيرات المستقلة وغير المستقلة. وقد تم تحديد ثمانية عشر مشعرا منها: العمر، الوزن، الخضاب، الكريات البيض، والاستجابة للعلاج الإشعاعي والكيماوي، الخضاب، الكريات البيض، الصفيحات الدمويّة، نوع الزرع ودرجة قربى المتبرع وغيرها. وقد بينت هذه الدراسة وفرزت كل من تلك المتغيرات المستقلة التي لها أثر واضح (ترابط) على كل تابع خرج غير مستقل مما سبق. بعدها أدخلت هذه المتغيّرات المترابطة إلى الشبكة العصبونيّة. حيث خصّصت 85% من عناصر العيّنة للتدريب و 5% للتحقّق و 10% للتجريب. بلغت دقة تنبّؤ الشبكة 88% وهي نسبة جيدة جدّاً وتحقّق هذا بعشرة عصبونات وعدد تكرارات لا تزيد عن 12. كما تناقص التدرج الانحداري لقيم جداً صغيرة (0.00125)، كذلك الحال مع معامل التّرابط (R= Regression) الذي بلغ حوالي 0.7، وهذا ينمّ على أنّ متغيّرات الدخل المترابطة هذه قادرة على تفسير النتائج بنسبة سبعين بالمائة وهذا بدوره أمر لم يكن متوافراً قبلاً للطبيب أثناء إعداد بروتوكولات العلاج المعتادة. وهكذا فقط حقق النظام الغاية المرجوة منه وهي توفير آليّة لدعم القرار مدير بنك الدم لتأمين كمية الدم المطلوبة لهذا العدد المتزايد من المرضى.